2008
DOI: 10.1074/jbc.m801902200
|View full text |Cite
|
Sign up to set email alerts
|

Double Deficiency of Tetraspanins CD9 and CD81 Alters Cell Motility and Protease Production of Macrophages and Causes Chronic Obstructive Pulmonary Disease-like Phenotype in Mice

Abstract: CD9 and CD81 are closely related tetraspanins that regulate cell motility and signaling by facilitating the organization of multimolecular membrane complexes, including integrins. We show that CD9 and CD81 are down-regulated in smoking-related inflammatory response of a macrophage line, RAW264.7. When functions of CD9 and CD81 were ablated with monoclonal antibody treatment, small interfering RNA transfection, or gene knock-out, macrophages were less motile and produced larger amounts of matrix metalloproteina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 46 publications
(54 reference statements)
7
70
0
Order By: Relevance
“…Elucidation of tetraspanin function using knockout mice can be complicated by functional redundancy between tetraspanins, which share relatively strong protein sequence identity. For example, CD9 and CD81 share 45% identity, and double-deficient mice have macrophage dysfunction leading to a phenotype that resembles chronic obstructive pulmonary disease; neither single knockout has detectable disease [54]. Tspan9 has relatively strong sequence identity with Tspan4 (55%) and CD53 (43%), for which knockout mice phenotypes have yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of tetraspanin function using knockout mice can be complicated by functional redundancy between tetraspanins, which share relatively strong protein sequence identity. For example, CD9 and CD81 share 45% identity, and double-deficient mice have macrophage dysfunction leading to a phenotype that resembles chronic obstructive pulmonary disease; neither single knockout has detectable disease [54]. Tspan9 has relatively strong sequence identity with Tspan4 (55%) and CD53 (43%), for which knockout mice phenotypes have yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…CD81 was shown to partially compensate for the fertilization defect observed in CD9-deficient mice (12). In addition, a role for these tetraspanins in the maintenance of normal lung function was only revealed by the observation of a chronic obstructive pulmonary disease-like phenotype in the double knock-out mouse but not in either of the single knockouts (44). Compensation between TspanC8 tetraspanins is likely to complicate future analyses of knockdown cells and knock-out animals.…”
Section: Discussionmentioning
confidence: 99%
“…Mice-CD9-KO and CD81-KO mice were provided by Dr. E. Mekada (Research Institute for Microbial Diseases, Osaka University, Osaka, Japan), and the generation of CD9/CD81-DKO mice was described previously (27). These mice were backcrossed more than eight generations into the C57BL/6J background in a barrier facility, and all of the animal procedures were performed in accordance with the Osaka University guidelines on animal care.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that CD9 and CD81 coordinately prevent the fusion of macrophages and that DKO mice develop an emphysematous lung phenotype (27,43). Hence, our present data suggest that both CD9 and CD81 additively function not only in macrophages, but also in LEC.…”
Section: Double Deletion Of Cd9 and Cd81 Impairs Lymphangiogenesis Unmentioning
confidence: 99%
See 1 more Smart Citation